PENGENALAN POLA SINYAL SEISMIK GUNUNG MERAPI DENGAN ALIHRAGAMGELOMBANG-SINGKAT - Saragih, Riko Arlando (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2008)
In most communication systems, speech was transmitted in narrowband frequency, mainly at frequency 300 Hz to 3400 Hz. Therefore, the frequencies outside this narrow bandwidth were lost. The lost frequencies can cause bias articulation in some speech.Bandwidth expansion is one technique to overcome this problem. Many bandwidth expansion techniques have been developed to increase the speech signal bandwidth on communication channels through envelope aliasing, nonlinear processing, and linear mo-del of human speech processing. Artificial Bandwidth Expansion (ABE) is one of the bandwidth expansion techniques to increase speech signal sampling frequency (upsampling) from 8 kHz to 16 kHz. The process annexes extra spectral components which are the images of the low frequency spectral components (narrowband) in the higher frequency segment. This method works frame by frame and each frame is 30 ms long and 5 ms overlapping with the adjacent frames. In this research, every frame was classified using Hidden Markov Model (HMM) and stated as sibilants or fricative consonants or stop consonants and treated separately (attenuated or amplified) according to the classification results.Comparison tests were done in this research based on the audio perceptions of so-me responders. Based on the results, it was acknowledged that the quality of the speech signal was significantly improved although some distortions were somewhat object-ttionable.